Obesity contributes to hepatocellular carcinoma development via immunosuppressive microenvironment remodeling - Yang, Jian; He, Jialuo; Feng, Yiting; Xiang, Ming (Frontiers in Immunology, 2023)
It is generally recognized that the initiation of obesity-related hepatocellular carcinoma (HCC) is closely associated with hepatic inflammation. However, the paradoxical role of inflammation in the initiation and progression of HCC is highlighted by the fact that the inflammatory HCC is accompanied by significant immune effector cells infiltration compared to non-inflammatory HCC and HCC with enhanced immune response exhibits better survival. Importantly, the cancer progression has been primarily attributed to the immunosuppression, which can also be induced by obesity. Furthermore, the increased risk of viral infection and thus viral-HCC in obese individuals supports the view that obesity contributes to HCC via immunosuppression. Here, we have reviewed the various mechanisms responsible for obesity-induced tumor immune microenvironment and immunosuppression in obesity-related HCC. We highlight that the obesity-induced immunosuppression originates from lipid disorder as well as metabolic reprogramming and propose potential therapeutic strategy for HCC based on the current success of immunotherapy.